2021
DOI: 10.1136/bmjopen-2020-042404
|View full text |Cite
|
Sign up to set email alerts
|

Psychological aspects in patients with advanced cancer receiving lifelong systemic treatment: protocol for a scoping review

Abstract: IntroductionA better understanding of the molecular, genetic and immunological characteristics of cancer and the introduction of new systemic treatment regimens in the last decades, has led to better treatment outcomes and increased survival rates for patients with previously short lived cancers. However, there is no uniform description to refer to this growing group of patients with advanced cancer who now respond to new systemic treatments for longer periods. Furthermore, little is known about the unique psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A recent scoping review of the psychosocial experiences of this population by Kolsteren and colleagues 10 concluded that uncertainty is the most prominent concern for this population at present but found no studies which examined it. Our review found two studies 6,36 which explored uncertainty qualitatively, but none quantitatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent scoping review of the psychosocial experiences of this population by Kolsteren and colleagues 10 concluded that uncertainty is the most prominent concern for this population at present but found no studies which examined it. Our review found two studies 6,36 which explored uncertainty qualitatively, but none quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many patients receiving IT or TT find themselves navigating a life characterized by an uncertain but terminal prognosis, for months or years 5–7 . This new treatment landscape has led to increasing calls to action from clinicians for an improved understanding of the experience of uncertainty and its impact on advanced cancer patients receiving IT or TT 5,7–10 . The predominant theory of illness uncertainty is Mishel's (1988 11 ) Uncertainty in Illness Theory, which defines uncertainty as “the inability to determine the meaning of illness‐related events” and accurately predict health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reporting of this review followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) reporting guidelines [ 17 , 18 ]. In this section, we provide a brief summary of these steps as an extensive description of the protocol has been previously published [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, psychosocial aspects are not limited to cancer patients but also to their caregivers, families, friends, and beyond colleagues and employers. As the impact on patients and their loved ones’ well-being and quality of life is expected to be considerable, it is crucial to examine these psychosocial outcomes to be able to support patients in their coping [ 9 ].…”
Section: Psychosocial Consequences Of a Cancer Diagnosismentioning
confidence: 99%